SKANDAL GAMESTOP: SEBUAH ANALISIS DESKRIPTIF & SOLUSI PENCEGAHAN DARI PERSPEKTIF EKONOMI POLITIK INVESTASI - Sutrisno Sutrisno; Bagus Panuntun; Fikri Irfan Adristi (Pascasarjana Universitas Halu Oleo, 2021)
GameStop Corp's financial scandal has rocked the world with enormous price increases caused by manipulation of information. This study aims to dissect, examine, and analyze prevention solutions from the financial scandal case. This research is a qualitative research with a descriptive approach. The research data were taken from the media, online newspapers, and several other relevant sources. The data analysis technique used in this study is the Miles and Huberman Model Data Analysis Technique. GameStop Corp.'s financial scandal case. is a financial scandal in the form of fraud and pump and dump behavior/asset price manipulation. A solution is needed to prevent cases of financial/corruption scandals with the main scheme through pump and dump behavior/asset price manipulation. Solutions to prevent pump and dump behavior/asset price manipulation include limiting predatory short sales on assets due to excess, especially “naked” short selling.